Veridicção e paixão na práxis enunciativa - Cortina, Arnaldo [UNESP] (2010)
The aim of this paper is to show how the methodological apparatus of Greimasian semiotics is applied to tackle discourse issues. In particular, focusing on the concepts of veridiction and passion, two specific discourse procedures, it is examined how these concepts are included in the enunciative praxis by analyzing two distinct texts: the short story “O cônego ou a metafísica do estilo”, by Machado de Assis, and the Nova Schin beer ad published in a Brazilian weekly magazine.